(untitled) (International Journal of Engineering and Computer Science, 2015)
The world wide web contains huge amount of data and it contains numerous websites that is examined by a tool or a program known as Crawler. Due to the richness of the information contributed by lots of internet users every day, internet forum sites have become valuable deposits of material on the web. As a result, mining knowledge from forum sites has become more important and more significant. The main objective of this paper is to focus on the web forum crawling techniques. In this paper, the various techniques of web forum crawler and challenges of crawling are discussed. The paper also gives the outline of web crawling and web forums.